PENGARUH PEMBERIAN LATIHAN HANDGRIP TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA PALEMBANG - Siska, Fera; Royani, Evi; Sherly Widianti (LPPM STIKes Mitra Adiguna, 2024)
According to WHO (World Health Organization) there are around one billion people in the world who suffer from hypertension. Hypertension is someone who experiences an increase in blood pressure above normal as indicated by the systolic and distolic numbers on a blood pressure examination. The aim of this research is to determine changes in blood pressure through handgrip workout s at the Harapan Kita Palembang elderly social institution in 2023. This research method is quantitative using a pre-experimental approach (One Group Pre-Post Test Design). The sample used in this research was purposive sampling. With a total of 12 elderly respondents. Based on the non-parametric statistical test (Wilcoxon) it is 0.000 p value 0.000 < 0.05) which means that it shows the influence of hand grip training on blood pressure values in elderly people with hypertension. There was a change in blood pressure after handgrip training, the subject was able to control blood pressure well. There is an influence of providing handgrip training. Based on the results of the Wilcoxon test, a p value of 0.000 <A 0.05 was obtained. It is hoped that we can examine other, more varied variables such as knowledge, behavior and cover a wide range of research using qualitative methods with in-depth interviews related to hypertension so that research on hypertension can continue to develop